Rational Proteomic Analysis of a New Domesticated Klebsiella pneumoniae x546 Producing 1,3-Propanediol - Xin Wang (Frontiers Media S.A., 2021)
In order to improve the capability of Klebsiella pneumoniae to produce an important chemical raw material, 1,3-propanediol (1,3-PDO), a new type of K. pneumoniae x546 was obtained by glycerol acclimation and subsequently was used to produce 1,3-PDO. Under the control of pH value using Na+ pH neutralizer, the 1,3-PDO yield of K. pneumoniae x546 in a 7.5-L fermenter was 69.35 g/L, which was 1.5-fold higher than the original strain (45.91 g/L). After the addition of betaine, the yield of 1,3-PDO reached up to 74.44 g/L at 24 h, which was 40% shorter than the original fermentation time of 40 h. To study the potential mechanism of the production improvement of 1,3-PDO, the Tandem Mass Tags (TMT) technology was applied to investigate the production of 1,3-PDO in K. pneumoniae. Compared with the control group, 170 up-regulated proteins and 291 down-regulated proteins were identified. Through Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway analysis, it was found that some proteins [such as homoserine kinase (ThrB), phosphoribosylglycinamide formyltransferase (PurT), phosphoribosylaminoimidazolesuccinocarboxamide synthase (PurC), etc.] were involved in the fermentation process, whereas some other proteins (such as ProX, ProW, ProV, etc.) played a significant role after the addition of betaine. Moreover, combined with the metabolic network of K. pneumoniae during 1,3-PDO, the proteins in the biosynthesis of 1,3-PDO [such as DhaD, DhaK, lactate dehydrogenase (LDH), BudC, etc.] were analyzed. The process of 1,3-PDO production in K. pneumoniae was explained from the perspective of proteome for the first time, which provided a theoretical basis for genetic engineering modification to improve the yield of 1,3-PDO. Because of the use of Na+ pH neutralizer in the fermentation, the subsequent environmental pollution treatment cost was greatly reduced, showing high potential for industry application in the future.